2016
DOI: 10.1177/0001839216663504
|View full text |Cite
|
Sign up to set email alerts
|

It’s about Time! CEOs’ Temporal Dispositions, Temporal Leadership, and Corporate Entrepreneurship

Abstract: How CEOs think and feel about time may have a big influence on their firms' strategies. We examine how two distinct CEO temporal dispositions-time urgency (the feeling of being chronically hurried) and pacing style (one's pattern of effort over time in working toward deadlines)-each influence corporate entrepreneurship, a key strategic behavior. We propose that CEOs' temporal leadership-how they manage the temporal aspects of top management teams' activities-mediates the relationships between their temporal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(172 citation statements)
references
References 175 publications
(360 reference statements)
7
165
0
Order By: Relevance
“…These studies have focused on executive personality captured through the Big Five dimensions (Herrmann & Nadkarni, 2014;Nadkarni & Herrmann, 2010), as well as other personality constructs, such as narcissism, hubris, and overconfidence (e.g., Chatterjee & Hambrick, 2007;Chen, Crossland, & Luo, 2015). More recent work in this area has focused on CEOs' values, such as political ideology (e.g., Christensen, Dhaliwal, Boivie, & Graffin, 2015), and cognitive aspects, such as temporal disposition (e.g., Chen & Nadkarni, 2017).…”
Section: Theoretical Background Upper Echelons Theorymentioning
confidence: 99%
“…These studies have focused on executive personality captured through the Big Five dimensions (Herrmann & Nadkarni, 2014;Nadkarni & Herrmann, 2010), as well as other personality constructs, such as narcissism, hubris, and overconfidence (e.g., Chatterjee & Hambrick, 2007;Chen, Crossland, & Luo, 2015). More recent work in this area has focused on CEOs' values, such as political ideology (e.g., Christensen, Dhaliwal, Boivie, & Graffin, 2015), and cognitive aspects, such as temporal disposition (e.g., Chen & Nadkarni, 2017).…”
Section: Theoretical Background Upper Echelons Theorymentioning
confidence: 99%
“…While, to the authors' knowledge, the studies that focus on "organizational culture" and CE in EMFs are quite limited, the list increases when we consider the role of leadership as a subset of the organizational culture of the firm. Considering the role of leadership in the firm in a notable study in Administrative Science Quarterly, Chen and Nadkami (2017), by focusing on small-and medium-sized Chinese firms, demonstrated that a chief executive officer's (CEO) temporal leadership plays a mediating role between the CEO's temporal dispositions and CE in terms of innovation, corporate venturing and strategic renewal activities. In a similar fashion, in a study of small and medium enterprises in Pakistan, Shafique and Kalyar (2018) showed that the type of leadership, in this case transformational leadership, positively affects CE and its dimensions of innovation, new business venturing, self-renewal, proactivity and risk-taking.…”
Section: Emerging Market Firms' Organizational Culture Leadership Anmentioning
confidence: 99%
“…Innovation strategy is the structural support to have innovation. The development of the innovation strategy would improve the capability of the company's management to have company's innovation (Chen & Nadkarni, 2017). Innovation refers to the tendency of the companies to do and support the new ideas, newness, experimentation and creative process that could have a new product, service and technology process as product (Covin & Lumpkin, 2011;Kuratko, 2010).…”
Section: Innovation Strategymentioning
confidence: 99%